Research on integrated communication and positioning technology based on visible light - Wei WANG; Jianping WANG; Lifang FENG; Jianli JIN (Dianxin kexue)
Visible light wireless technology transmits information through visible light, utilizing light-emitting diode (LED) light sources to achieve communication and positioning while illuminating.Visible light communication positioning integration (VLCP) technology is one of the key supporting technologies for future large-scale Internet of things (IoT) applications.Orthogonal frequency division multiplexing (OFDM) technology can be used to allocate different spectral resources to visible light communication (VLC) and visible light positioning (VLP) systems, while achieving communication and positioning functions.Resource allocation is the key to improving the efficiency of VLCP systems and expanding their applicability.A new resource allocation method based on error vector magnitude(EVM) was proposed.EVM was utilized to allocate subcarriers for positioning and communication in VLCP systems, communication and positioning performance was dynamically adjusted based on channel parameters, system quality of service (QoS) was ensured, and system channel utilization was improved.The experimental results indicate that at 1.5 m×1.5 m×1.5 m indoor environment, the proposed resource allocation algorithm can improve channel utilization by at least 19.5% compared to fixed resource allocation algorithms.Under the premise of comparable performance to algorithms that use signal-to-noise ratio (SNR) for resource allocation, it greatly saves system resources and is easy to apply in practice.